The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/d0gc01544j
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle based alternatives assessment (LCAA) for chemical substitution

Abstract: The world faces an increasing need to phase out harmful chemicals and design sustainable alternatives across various consumer products and industrial applications. Alternatives assessment is an emerging field focusing on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 65 publications
0
33
0
Order By: Relevance
“…Such improvements are mainly related to increasing the spatiotemporal and population-level resolution of impact estimates and extending the coverage and quality of substance, exposure, and dose-response information (Fantke et al 2018a,b;Kirchhübel & Fantke 2019;Crenna et al 2020;Gentil et al 2020;Holmquist et al 2020). Furthermore, a series of recent studies has demonstrated that environmentally mediated exposure from chemical emissions is less important for overall exposure than consumer exposure to chemical constituents in products (Shin et al 2015;Ernstoff et al 2016;Csiszar et al 2017;Ring et al 2019;Fantke et al 2020b;Jolliet et al 2021). Hence, including pathways related to chemicals in consumer products into toxicity characterization frameworks is crucial for considering all relevant pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Such improvements are mainly related to increasing the spatiotemporal and population-level resolution of impact estimates and extending the coverage and quality of substance, exposure, and dose-response information (Fantke et al 2018a,b;Kirchhübel & Fantke 2019;Crenna et al 2020;Gentil et al 2020;Holmquist et al 2020). Furthermore, a series of recent studies has demonstrated that environmentally mediated exposure from chemical emissions is less important for overall exposure than consumer exposure to chemical constituents in products (Shin et al 2015;Ernstoff et al 2016;Csiszar et al 2017;Ring et al 2019;Fantke et al 2020b;Jolliet et al 2021). Hence, including pathways related to chemicals in consumer products into toxicity characterization frameworks is crucial for considering all relevant pathways.…”
Section: Introductionmentioning
confidence: 99%
“…High throughput quantitative exposure assessment is performed according to the product intake fraction (PiF) framework (Fantke et al., 2016; Fantke, Huang et al. 2020; Jolliet et al., 2015) and its implementation within the USEtox model, successively determining the amount of chemical applied in product per user and per day, the corresponding exposure in mg/kg/d and the associated risks, hazard quotients, or health impacts (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…These data and product usage methods have been used within a screening‐level exposure model to inform chemical prioritization (Isaacs et al., 2014), which had some limitations on the exposure side, including lower‐tier conservative assumptions that do not account for the mass balance nature of competing processes, such as volatilization and dermal uptake on skin surface. On the other hand, more elaborate, higher tier mass balance‐based models have been developed to estimate transport, fate, exposure associated with multiple chemical emissions, and usage along the life cycles of products and services (Csiszar, Ernstoff, Fantke, Meyer, & Jolliet, 2016; Fantke, Ernstoff, Huang, Csiszar, & Jolliet, 2016; Fantke, Huang, Overcash, Griffing, & Jolliet, 2020) for high‐throughput screening of cosmetics, and have been consolidated within an extended USEtox near‐field and far‐field model, but to date have incorporated relatively limited data on chemical and product usage.…”
Section: Introductionmentioning
confidence: 99%
“…A recent multiphase project to identify a resin for additive manufacturing safer than those currently used in stereolithography provides an example of applying a life cycle‐based approach to understanding the exposure potential for various stakeholders at different stages as well as a methodology for comparing impacts across all life cycle stages of the resin (Overcash ). Presenters noted the potential that life cycle‐based methods, paired with high throughput exposure and toxicity approaches, can play in addressing data gaps in alternatives assessment (Fantke et al ; Overcash et al ).…”
Section: Advancing the Science Of Alternatives Assessmentmentioning
confidence: 99%